POTENSI LIMBAH PADI SEBAGAI PAKAN SAPI BALI DI DESA SUKOHARJO II KECAMATAN SUKOHARJO KABUPATEN PRINGSEWU - Faisal Abdul Azis; Liman .; Yusuf Widodo (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
The objective of the research were to study potency of rice by produce and its carryingcapacity in Sukoharjo II Village Sukoharjo Sub-District Pringsewu District. This research wasconducted in may 2013 located in Sukoharjo II Village Sukoharjo Sub-District Pringsewu District.The methode of purposive sampling was used in the research. The Date used in this studyconsisted of prime and secondary date. The prime date consist of agricultural land, harvested ricearea, product of rice mill, and product of straw. Secondary date consist of information aboutagricultural potency and animal husbandry potency in Sukoharjo II Village Sukoharjo SubDistrictPringsewu District.The result of this research showed that the straw can produce 683.537,4 kg/year and ricebran 64.920 kg/year based on dry matter. The waste production of straw with range 40 % for feedand rice bran with range of 50% for feed. Sukoharjo II Village Sukoharjo Sub-District PringsewuDistrict can produce 752.957,4/kg/th waste of rice. Totaly for Carrying capacity of waste rice inSukoharjo II Village Sukoharjo Sub-District Pringsewu District were 371 UT/th.